Pengembangan UMKM Berbasis Teknologi untuk Meningkatkan Daya Saing di Pasar Global - Ferdiansyah Himawan; Rendi Rendi; Ahmad Wijayanto; Masnama. K (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, small, and medium enterprises (MSMEs) play a strategic role in supporting the local economy, but still face limitations in the use of technology and market expansion. The Banana Chip MSME (Toko Agung) in Banatorejo Village, Tapango District, Polewali Mandar Regency is one of the local food businesses that has potential, but its management is still traditional. This community service activity aims to develop technology-based MSMEs to increase product competitiveness. The methods used are participatory assistance through observation, interviews, training, and evaluation, with a focus on digital marketing, packaging and branding improvements, and strengthening simple business management. The results of the activity showed an improvement in packaging quality, expansion of marketing reach through digital media, and improvements in business financial record keeping. Technology-based development has a positive impact on the readiness of MSMEs to face broader market competition. The implications of this activity show that integrated technology assistance can be an effective strategy in increasing the competitiveness and sustainability of local food MSMEs.